Decommodifying Platform Work through an EU Definition of Worker (Glocalism: Journal of Culture, Politics and Innovation, 2022)
This article aims to highlight the process of recommodification characterizing the new forms of work today, in particular gig economy jobs, and the possible solutions that can be suggested to guarantee adequate protection. After having explained the importance of labour law to decommodify the new forms of work, in particular platform work, this article explains the different ways to legally classify them at the national level and the relevant contribution an EU definition of worker could bring to address the problem of recommodification. In doing this, the article also mentions some relevant aspects of the EU proposal for a directive in the field.
Keywords: recommodification; gig economy; labour law; decommodification; EU